2006
DOI: 10.1016/j.jet.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Learning dynamics for mechanism design: An experimental comparison of public goods mechanisms

Abstract: In a repeated-interaction public goods economy, dynamic behavior may affect the efficiency of various mechanisms thought to be efficient in one-shot games. Inspired by results obtained in previous experiments, the current paper proposes a simple best response model in which players' beliefs are functions of previous strategy profiles. The predictions of the model are found to be highly consistent with new experimental data from five mechanisms with various types of equilibria. Interesting properties of a 2para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 34 publications
0
46
1
Order By: Relevance
“…A nonlinear adjustment process is preferred over a linear adjustment process, since this allows for a rapid learning in the first rounds. 12 In any case, results do not depend on this specification. We get the same results if we instead add "round."…”
Section: Time Trends Testing For Adjustments In Bidding Over Time Fomentioning
confidence: 83%
“…A nonlinear adjustment process is preferred over a linear adjustment process, since this allows for a rapid learning in the first rounds. 12 In any case, results do not depend on this specification. We get the same results if we instead add "round."…”
Section: Time Trends Testing For Adjustments In Bidding Over Time Fomentioning
confidence: 83%
“…We estimate the parameter values by fitting the model to the individuals' data in the WGO experiments (we obtained the data through personal communication with Prof. James Walker) to check if the data are consistent with our theory. Healy (2006) provides experimental evidence to support a "k-period average" model, in which players form their beliefs at the current period, based on the observations in the previous k periods. Here, we instead use a time-weighted average to model the belief formation (cf., Cheung and Friedman 1997).…”
Section: Statistical Analysis Of the Wgo Datamentioning
confidence: 90%
“…Experiments provide a hint as to the solution to this problem. In their experiments, Healy (2006) and Healy and Mathevet (2012) implemented five types of public goods mechanisms, including the voluntary contribution mechanism. They found that subjects apparently adopt myopic responses to the decisions by the other players in the previous round, or in some recent rounds.…”
Section: Introductionmentioning
confidence: 99%
“…Healy (2006) shows that participants best respond to the last observation they are making in a repeated game. Güth, Koukoumelis et al (2014) investigate in which ways the reactions of experimental participants to mechanisms depend on them being perceived as fair.…”
Section: If Additionally Individuals Can Misrepresent Their Types ?mentioning
confidence: 99%